Study & analysis of cryptography algorithms : RSA, AES, DES, T-DES, blowfish - Singh, Pankaj; Kumar, Sachin (International Journal of Engineering and Technology, 2017)
Cryptography is about protecting the data from third parties or from public to read confidential data. Cryptography mainly focuses on encrypting the data or we can say converting the data and decrypting the actual data or we can say reconverting the data by different methods. These encryption and decryption methods are based on mathematical theories and are implemented by computer science practices. But as cryptography progressed ways were found to decode the secured data and view actual data. This was also done by the use of mathematical theories and computer science practices. Popular algorithms which are used in today’s world are, AES (Advance Encryption Standard), Blowfish, DES (Data Encryption Standard), T-DES (Triple Data Encryption Standard), etc. Some of the previously known algorithms were RSA (Rivest–Shamir–Adleman), ECC (Elliptic curve cryptography), etc. These algorithms have their own advantages and drawbacks. But as people were progressing more in breaking them down, these algorithms were supported by digital signatures or hash done by different algorithms like MD5, SHA, etc. By these means data integrity, data confidentiality, and authentication of data are maintained. But as the things are progressing it seems that new advancements are always needed in the field of cryptography to keep the data secure.
Keywords: Encryption; Decryption; Cryptography; AES; DES; RSA; Blowfish; Triple-DES